Pelatihan Perbanyakan Pupuk Hayati Mikoriza Kepada Kelompok Tani Desa Karangsari Kecamatan Darma Kabupaten Kuningan - Ai Nurlaila; Dede Kosasih; Nina Herlina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Kuningan, 2022)
Problems in agricultural, plantation and forestry cultivation that are often faced by farmers in Karangsari Village include high dependence on subsidized fertilizers, pests and diseases, climate/weather uncertainty, and market prices. To overcome this problem, various potential bioprospectives available in nature can be used, both acting as soil enhancers, biological fertilizers, organic fertilizers, controlling pests and diseases, and others. One of the bioprospecting materials in the Gunung Ciremai National Park area is Arbuscular Mycorrhizal Fungi (AMF). The purpose of this service is to provide understanding and skills of farmers in the use of natural resources for plant cultivation activities, especially in terms of propagation of mycorrhizal fertilizers. the method of devotion is carried out by means of lectures and practices. The lecture method is used to deliver material about natural ingredients that can be used as fertilizer and pest and disease control, while the practice/training method is used to train mycorrhizal biofertilizer propagation techniques. The results of the service show that farmers are very enthusiastic in responding to this activity, as can be seen from the many mycorrhizal discussions which are new knowledge for them. The participants tried to multiply mycorrhizae in a simple way and maintain the plants until harvest time. Farmer groups are also trying to use mycorrhizae in their fields.